Uric Acid and Nutrient Intake of Adolescent Soccer Players in Yogyakarta - Puspaningtyas, Desty Ervira; Afriani, Yuni (Department of Physical Education, Sport, Health and Recreation, 2020)
The aim of this study was to view uric acid levels and nutrient intake of soccer players. This study examined the uric acid level differences based on nutrient intake of adolescent soccer players. Indeed, nutritional status monitoring is needed to evaluate health status which can contribute to athletes’ performance. This was an observational study conducted at SSB Real Madrid in April-September 2017. Subjects involved in this study were 27 active joined U-13 or U-16 in SSB Read Madrid UNY, Yogyakarta. Uric acid data were obtained by measuring peripheral blood sample. Nutrient intake data were obtained by using SQFFQ form. The differences in uric acid levels based on nutritional intake category were tested using ANOVA test. The average of uric acid levels were 6.72±1.21 mg/dl with average protein intake of 87.38±27.41 grams. The average of energy, fat, and carbohydrate intake was 2,189.02±464.87 kcal, 46.92±15.75 grams, and 365.61±82.32 grams. There was no difference in uric acid levels based on energy, protein, fat, and carbohydrates intake (p=0.216; p=0.489; p=0.587; and p=0.845) of adolescent soccer players. The clearance of uric acid, the amount and type of fluid intake, the type of animal protein, and the purine-source food probably contributed to athletes’ uric acid levels.